+0  
 
0
258
2
avatar+70 

Simplify f(x+h)-f(x)/ h

where (f)x=2x+ x

Thank you 

Ashreeta  Aug 28, 2017
 #1
avatar+19638 
+2

Simplify f(x+h)-f(x)/ h

where (f)x=2x2 + x

 

\(\begin{array}{rcll} f(x) &=& 2x^2+x\\ f(x+h)&=&2(x+h)^2+(x+h)\\\\ \text{The difference quotient is:}\\ \dfrac{\Delta y}{\Delta x} &=& \dfrac{f(x+h)-f(x)}{h}\\ &=& \dfrac{2(x+h)^2+(x+h)-(2x^2+x)}{h}\\ &=& \dfrac{2(x+h)^2+ x +h-2x^2 - x }{h}\\ &=& \dfrac{2(x+h)^2 +h-2x^2 }{h}\\ &=& \dfrac{2(x^2+2xh+h^2) +h-2x^2 }{h}\\ &=& \dfrac{2x^2+4xh+2h^2 +h-2x^2 }{h}\\ &=& \dfrac{ 4xh+2h^2 +h }{h}\\ &=& \dfrac{ h( 4x+2h +1) }{h}\\ \dfrac{\Delta y}{\Delta x} &=& 4x+2h +1 \end{array} \)

 

 

\(\begin{array}{rcll} f'(x) &=& \dfrac{dy}{dx} \\ \dfrac{dy}{dx} &=& \lim \limits_{h\to 0} { \left( 4x+2h +1 \right) } \\ \dfrac{dy}{dx} &=& \left( 4x+2\cdot 0 +1 \right) \\ \dfrac{dy}{dx} &=& \left( 4x+1 \right) \\\\ \mathbf{f'(x)} &\mathbf{=}& \mathbf{4x+1} \end{array}\)

 

laugh

heureka  Aug 28, 2017
 #2
avatar+70 
+2

Thank you 

Ashreeta  Aug 28, 2017

7 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.